Eosinophils Target Therapy for Severe Asthma: Critical Points. (25th October 2018) - Brussino, L.; Heffler, E.; Bucca, C.; Nicola, S.; Rolla, G.
Abstract : Asthma is a chronic and heterogeneous disease, which is defined as severe disease whenever it requires treatment with a high dose of inhaled corticosteroids plus a second controller and/or systemic corticosteroids to prevent it from becoming ''uncontrolled'' or if it remains ''uncontrolled'' despite this therapy. Severe asthma is a heterogeneous condition consisting of phenotypes such as eosinophilic asthma, which is characterized by sputum eosinophilia, associated with mild to moderate increase in blood eosinophil count, frequently adult-onset, and associated with chronic rhinosinusitis with nasal polyps in half of the cases. Eosinophilic asthma is driven by T2 inflammation, characterized, among the others, by interleukin-5 production. IL-5 plays a key role in the differentiation, survival, migration, and activation of eosinophils, and it has become an appealing therapeutic target for eosinophilic asthma. In recent years two monoclonal antibodies (mepolizumab and reslizumab) directed against IL-5 and one monoclonal antibody directed against the alpha-subunit of the IL-5 receptor (benralizumab) have been developed. All these IL-5 target drugs have been shown to reduce the number of exacerbation in patients with severe asthma selected on the basis of peripheral blood eosinophil count. There are still a number of unresolved issues related to the anti-IL5 strategy in eosinophilic asthma, which are here reviewed. These issues include the effects of such therapy on airway obstruction and asthmatic symptoms, the level of baseline eosinophils that predicts a response to treatment, the relationship between blood and airway eosinophilia, and, perhaps most importantly, how to elucidate the pathogenetic role played by eosinophils in the individual patient with severe eosinophilic asthma.